Seroprevalence, Knowledge, Attitude and Practice Regarding Prevention of Hepatitis C among Municipal Waste Collectors in Penang Island, Malaysia / Surajudeen Abiola Abdulrahman ...[et al.] - Abdulrahman, Surajudeen Abiola; Kader Maideen, Siti Fatimah; Rahim, Fairuz Fadzilah; Rashid, Abdul (Universiti Teknologi MARA Cawangan Selangor, 2019)
Introduction: This study aimed to determine the prevalence of Hepatitis C infection and the level of knowledge, attitude and practice regarding Hepatitis C prevention among municipal waste collectors in Penang Island, Malaysia. Methods: A cross-sectional study was conducted among a convenient sample of 184 adult male municipal waste collectors in Penang Island from January to May 2018. Respondents' blood samples were obtained and evaluated for antibodies to Hepatitis C virus (anti-HCV), and questionnaires administered to them to collect information on sociodemographic variables and knowledge, attitude and practice regarding Hepatitis C prevention. The seroprevalence of Hepatitis C virus was estimated, and the association between sociodemographic variables and respondents' level of knowledge, attitude and practice regarding Hepatitis C prevention was explored using a range of parametric and non-parametric statistical tests in SPSS version 23. Results were considered significant at p<0.05. Results: The seroprevalence of Hepatitis C infection among our study sample was 0%. Majority had good attitude (60.9%) and good practice (70.1%) but poor knowledge (72.8%) of Hepatitis C. Respondents' income was significantly predictive of knowledge (p=0.033) and attitude (p=0.005) regarding Hepatitis C prevention. There were no significant associations between sociodemographic factors and practice regarding Hepatitis C prevention. There was a significant positive correlation between respondents' knowledge and practice regarding Hepatitis C prevention (r=0.169, p=0.022). Conclusions: Knowledge of Hepatitis C prevention is significantly lacking among Municipal waste collectors in Penang Island, and their income appears to play a significant role in determining their level of knowledge and attitude regarding Hepatitis C prevention.